Synthesis of Dimensions, Indicators, and Components of Appropriate Educational Leadership for Blended Learning (In-Person and Virtual) in Elementary Education - Saraei, Pari; Maleki Avarsin, Sadegh; Yari Haj Ataloo, Jahangir (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2025)
Objective: The present study aimed to synthesize the dimensions, indicators, and components of appropriate educational leadership for blended learning (in-person and virtual) in elementary education. Methodology: The present study was qualitative and of the synthesis type. The statistical population of the research comprised existing studies from 2013 to 2023. In total, the number of articles and studies related to the keywords was 1,315 (69 Persian articles and 1,246 English articles). Out of this number, 26 studies (22 English studies and 4 Persian studies) were selected for final analysis based on exclusion criteria. The research data were analyzed using Roberts’ six-step synthesis model, employing three-stage coding (open, axial, and selective). Findings: The data were identified in the form of 162 open codes, 24 axial codes, and 7 selective codes. The dimensions identified include competent leadership, organizational dimensions, technology, philosophical and epistemological systems, learning environment, learning outcomes, and evaluation systems. Conclusion: Identifying the dimensions, indicators, and components of appropriate educational leadership for blended learning in elementary education can play a significant role in designing an appropriate model for this stage.